Information technology: marriage between it and social business-grameen intel social business ltd. - Nahiduzzaman, Kh Md; Munni, Sheikh Rubaiya Sultana (Social Business: Theory, Practice, and Critical Perspectives, 2016)
Aiming to reduce infant mortality, improve the mother’s health, and help Bangladeshi rural farmers improve agricultural production, Grameen Intel Social Business Limited was formed in 2009 by Grameen Trust and Intel – linking an organization with decades of experience in addressing poverty to a company with decades of know-how in technology innovation. Grameen Intel is devoted to looking at different ways and means to assist the rural poor by investigating their real needs to find suitable solutions using information and technology (IT). In the agriculture care program, mrittika analyzes soil nutrients to find the deficit nutrition required for enhanced production while ankur is a seed selection application for the rural farmers. Under maternal health programs, shumata is ante-natal care monitoring and tracking software for pregnant women, and dolna is a vaccine scheduling and tracking software for newborns and infants. Given this background, this part of the book attempts to discuss these ongoing programs to view the current and potential effects on the villagers. Moreover, a critical look is given on the geographic dissemination, costs associated with these services and actual benefits.